Poems for Donald Nicholl - Evans, Charles (New blackfriars, 1997)
Donald Nicholl (1923-97), born in Halifax, Yorkshire, won a scholarship to Balliol College, Oxford but was called up in 1942 and served in the Far East. On returning to Oxford he was received into the Roman Catholic Church at Blackfriars, by Fr Richard Kehoe, in 1946. The following year he married Dorothy Tordqff, whom he had known since school days and who had found her own way to Catholicism. Conrad Pepler, Victor White and Illtud Evans, as well the library at Blackfriars, Oxford, the chaplaincy at 24 George Square, Edinburgh (where Anthony Ross became a friend), and Spode House, Staffordshire constituted the Dominican part of his world A distinguished medievalist (his life of Archbishop Thurston of York appeared in 1964), Donald taught at Edinburgh and Keele, before switching his interests to the twentieth century and to Russia in particular and moving to a chair in history and religious studies in California at Santa Cruz. His last academic post was as Rector of the Ecumenical Institute at Tantur, near Jerusalem. With Holiness (1981), The Testing of Hearts (1989), Triumphs of the Spirit in Russia (1997) and The Beatitude of Truth (forthcoming), his guidance in the life of the spirit will not be forgotten.